The role of accounting employees’ information security awareness on the intention to resist social engineering - Senduk, Rian Candy; Kurniawan, Yohannes (Edelweiss Applied Science and Technology, 2025)
The growing reliance on technology in accounting has boosted productivity but also increased vulnerability to cyber threats, particularly social engineering attacks that exploit human weaknesses to access sensitive data. This study evaluates and enhances security awareness among accounting employees to mitigate risks for individuals and organizations. Using a questionnaire survey and SmartPLS 4.1.0.9, it tests 12 hypotheses derived from prior research, assessing the Theory of Planned Behavior’s applicability in explaining employees’ resistance to social engineering. The study focuses on accountants in medium-to-large firms in Indonesia’s Jabodetabek region, including senior managers, first-level managers, and entry-level employees, with an emphasis on recent five-year data breaches. Results show high overall security awareness, but six hypotheses were insignificant, indicating that TPB does not fully explain employees’ intentions to counter such threats. While findings underscore strong awareness, the partial support for TPB highlights the need for further research on behavioral influences. The study stresses the importance of organizational and individual vigilance in safeguarding credentials, urging accountants to adopt proactive measures against social engineering. It also lays the groundwork for future research on improving cybersecurity performance in accounting. Given limited prior studies on accounting-specific security awareness, this work offers key insights for practitioners and academics.